The Impact of Teaching Coping Skills in Schools on Youth Mental Health and Academic Achievement: Evidence from a Field Experiment - Mari Rege; Edvin Bru; Ingeborg F. Solli; Maximiliaan W. P. T. Thijssen; Kjersti B. Tharaldsen; Lene Vestad; Sigrun K. Ertesvåg; Terje Ogden; Paul N. Stallard (CESifo GmbH, 2025)
Effective and scalable strategies for promoting youth mental health are urgently needed. We conducted a randomized controlled trial to assess the impact of school-based, teacher-led coping skills instruction on youth mental health and academic achievement. The trial included 84 classes and 1,879 ninth-grade students (ages 14–15) in Norway. Findings indicate improved mental well-being and reduced emotional distress at a one-year follow-up, particularly among students with low baseline well-being. The intervention also enhanced academic motivation and increased the likelihood of choosing an academic high school track. Additionally, it had a positive effect on math performance among students with initially low academic motivation, but no significant effects on performance in English or Norwegian.
Keywords: I20; J00; 330; social and emotional skills; preventive mental health policy; school-based intervention; teacher led intervention; education policy